FACTORS AFFECTING DIVIDEND PAYOUT RATIO OF HIDIV20 INDEX FIRMS - CEIN CHRISTINE; Erika Jimena Arilyn (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research are conducted with the purpose to test factors that affect of independent variables tested are Return on Equity, Return on Asset, Debt to Equity, Growth, and Firm Size on Dividend Payout Ratio. The population studied in this research was firms listed on HIDIV20 Index member. Sample tested in this research were 6 firms that fulfill the sample selection criteria with purposive sampling method. Data analysis are conducted using multiple regression method. The result of this research shows that Return on Equity have positive effect on Dividend Payout Ratio. While Return on Asset, Debt to Equity, and Growth have negative effect and Firm Size has no effect to Dividend Payout Ratio.